PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP PROFITABILITAS DENGAN RISIKO PEMBIAYAAN SEBAGAI VARIABEL INTERVENING PADA BANK UMUM SYARIAH PERIODE 2017-2021 - Muhammad Alwi Setiawan; M. Ridwan; Khairina Tambunan (LPPM - STIE SAKTI ALAM KERINCI, 2023)
Research was conducted to analyze the influence of Good Corporate Governance on Profitability which is intervened through the Problematic Financing Variable. The research is quantitative research. The population in this study was 14 Sharia Commercial Banks. Using the Purpose Sampling sampling technique, a sample of 10 Islamic commercial banks was taken. This research is panel data research using path analysis techniques. The research results show that partially, Good Corporate Governance does not have a significant effect on Financing Risk which is proxied by Non Performing Financing (NPF) and Profitability which is proxied by Return On Assets (ROA). Financing Risk which is proxied by Non Performing Financing (NPF) partially has a significant effect on Profitability which is proxied by Return On Assets (ROA). And indirectly, Good Corporate Governance has a significant effect on Financing Risk which is proxied by Non Performing Financing (NPF) through Profitability which is proxied by Return On Assets (ROA).